The exact and numerical solitary-wave solutions for generalized modified Boussinesq equation - Kaya, D (Elsevier, 2006)
In this study, a decomposition method for approximating the solution of the generalized modified Boussinesq equation is implemented. By using this scheme, explicit exact solution is calculated in the form of a convergent power series with easily computable components. To illustrate the application of this method, numerical results are derived by using the calculated components of the decomposition series. The obtained results are found to be in good agreement with the exact solution. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: decomposition method; generalized modified Boussinesq equation; traveling wave solution; solitary wave solution